Critique and Political Argumentation. (September 2013) - Finlayson, Alan
If political philosophy begins with Plato then it begins with anxiety over linguistic ambiguity – with an attempt to establish fixed definitions of words and to assign the right of rule to those best able to contain and order meaning. In the present day philosophers and social scientists remain deeply interested in language – but where Plato wanted to regulate the form and content of stories, substitute private dialogue for public speech and ban the unruly art of writing, contemporary philosophers are generally concerned with the establishment of public reason, specification of the principles that might govern our societal communications and explication of the uses, effects and histories of particular kinds of language.